Placements of loans of the Tacna region multiple banking, before and after the measures for the sanitary emergency - Peñaloza Arana, Eloyna Lucia (2022)
Taking into account the health emergency at the national level that dictates prevention and control measures for Covid 19 in the country and the consequent paralysis and/or decrease in economic activities, the present research aimed to determine the performance of credit placements of the Multiple banking in the Tacna region, before and after the measures for the health emergency. The methodology had a quantitative approach, basic type, non-experimental design, longitudinal due to it compared two groups of 20 months each one. It established that there are differences between credit placements by multiple banks in the Tacna region before and after the measures were taken due to the health emergency due to Covid 19. The results determined that the mean for the first group called credit placement by multiple banks in the Tacna region before the health emergency measures is 1,553,854.1380, while for the credit placement group by multiple banks in the Tacna region after the health emergency measures, they have an average of 1,831,637.4890, with significant differences in the comparison periods for the variable under study.